2019
DOI: 10.1016/j.heliyon.2019.e01138
|View full text |Cite
|
Sign up to set email alerts
|

Risks related to the lack of lubrication on surface integrity in drilling

Abstract: Drilling processes can significantly affect the surface integrity of metallic components. Thus, the control of the drilling process is of great interest for industry to ensure a satisfactory surface behavior. The understanding of such a process is complex because the hole is confined. Therefore, the physical phenomena are not easily observable during a drilling operation. The aim of this article is to present an experimental investigation on the effect of the drilling conditions for the machining of an austeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They found the margin textured tool the most efficient, which reduces thrust force 10-12 %, 15-20 %, 15-19 % in dry, wet, and MQL conditions, respectively. Again, Girinon et al, [52] explored 316L austenitic stainless steel drilling under dry, internal and external coolant systems. The results showed that the dry condition is severe for temperature, forces, and chip tectonics.…”
Section: Mql In Drillingmentioning
confidence: 99%
“…They found the margin textured tool the most efficient, which reduces thrust force 10-12 %, 15-20 %, 15-19 % in dry, wet, and MQL conditions, respectively. Again, Girinon et al, [52] explored 316L austenitic stainless steel drilling under dry, internal and external coolant systems. The results showed that the dry condition is severe for temperature, forces, and chip tectonics.…”
Section: Mql In Drillingmentioning
confidence: 99%
“…It should be noticed that industrial drilling processes are often used with lubrication systems as studied by Pimenov et al [7]. The effect of lubricant has been studied by Girinon et al [8] and it has been shown that lubrication avoids producing tensile residual stresses on the hole surface. Nevertheless, recycling lubricants is nowadays both a complex and energy intensive problem from the ecological point of view.…”
Section: Introductionmentioning
confidence: 99%
“… Girinon et al. (2019) worked on drilling process control for surface integrity of metallic components with an austenitic stainless steel 316L used as a case study.…”
Section: Introductionmentioning
confidence: 99%